Level of training needs of the teachers’ have in the integration schools in Makkah from the teachers’ point of view - ALoufi, Salem Humaidan (Journal of Educational and Psychological Sciences, 2020)
This research aims to identify the training needs in the specialized field, the educational field and the personal field of teachers of integration schools from their point of view. The research followed the descriptive approach and the study population reached (112) teachers and the questionnaire was used as a tool to collect the information and data necessary to answer the study questions. The research concludes with a number of results, the most prominent of which are: methods of communication with students of special education, And the modification of the behavior of students with special needs, as well as the use of means and assistive devices applicable to students of special education, as well as ways of dealing with special education teachers with disabilities according to areas of disability and degrees, as well as methods of integrating people with special needs in the school environment and identify the patterns of personality of special education students, and the development of trends Positive with special education students with positive relationships with special education students. The research concludes with a set of recommendations, including: Training courses in the specialized field in relation to the use of means and assistive devices applicable to students of special education, as well as training courses in the educational field with regard to modifying the behavior of special education students, and working to modify negative trends.
Keywords: Training needs; Students with special needs; positive and negative trends; makkah